Domperidone Prescribing Practices Exposed Patients to Cardiac Risk despite a "Black Box" Warning: A Canadian Tertiary Care Center Study. (24th February 2016) - Forbes, Nauzer; Cooray, Mohan; Al-Dabbagh, Raed; Yuan, Yuhong; Tse, Frances; Liu, Louis W. C.; Xenodemetropoulos, Ted
Abstract : Background. In 2012, Health Canada released a warning regarding domperidone use, based on associations with life-threatening arrhythmias and death. Objective. This study aimed to compare the appropriateness of domperidone prescribing patterns before the advisory to those afterward. Methods. Two retrospective reviews were conducted for patients prescribed domperidone during quarters in 2005 and 2012. Outcomes included appropriateness of indication, dosing regimens, monitoring of electrolytes, baseline electrocardiogram performance and characteristics, presence of left ventricular dysfunction, and coprescription of QT-prolonging medications. Univariable and multivariable logistic regression analyses were performed.p values < 0.05 were considered significant. Results. 290 and 287 patients were analyzed in 2005 and 2012, respectively. Domperidone initiation in hospital decreased from 2005 to 2012 (71.4% versus 39.4%, p < 0.0001 ) as did prescriptions for nonapproved indications (84.8% versus 58.2%, p < 0.0001 ). In-hospital initiation predicted prescription for nonapproved indications (OR = 7.01, 95% CI 4.52–10.87, p < 0.0001 ). Use of domperidone as the sole GI drug predicted nonapproved indications (OR = 2.51, 95% CI 1.38–4.55, p = 0.002 ). Conclusions. The advisory was associated with more appropriate domperidone initiation and compliance with recommended dosages. Our study suggests the need for increased awareness of the dosing and monitoring of domperidone to ensure patient safety.